2010
DOI: 10.1021/jp1047166
|View full text |Cite
|
Sign up to set email alerts
|

Isomerization of Neopentyl Chloride and Neopentyl Bromide by a 1,2-Interchange of a Halogen Atom and a Methyl Group

Abstract: The recombination of chloromethyl and t-butyl radicals at room temperature was used to generate neopentyl chloride molecules with 89 kcal mol(-1) of internal energy. The observed unimolecular reactions, which give 2-methyl-2-butene and 2-methyl-1-butene plus HCl, as products, are explained by a mechanism that involves the interchange of a methyl group and the chlorine atom to yield 2-chloro-2-methylbutane, which subsequently eliminates hydrogen chloride by the usual four-centered mechanism to give the observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…[1][2][3][4][5][7][8][9][10][11] Scanning Tables 1 and 2 suggests that the interchange of Cl or Br might be observed with all of the groups in Table 1 results confirm E 0 (Cl-CH 3 ) = 259 kJ/mol for the CH 3 -Cl interchange reaction for 2,2-dimethyl-1chloropropane; i.e., two methyl groups replace two hydrogen atoms on C-2 of 1-chloropropane. 20 In addition, reactions with E 0 (interchange) > 290 kJ/mol might be observed for photochemical and thermal activation methods that prepare reactants with energy greater than 400 kJ/mol.…”
Section: R a F Tmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][7][8][9][10][11] Scanning Tables 1 and 2 suggests that the interchange of Cl or Br might be observed with all of the groups in Table 1 results confirm E 0 (Cl-CH 3 ) = 259 kJ/mol for the CH 3 -Cl interchange reaction for 2,2-dimethyl-1chloropropane; i.e., two methyl groups replace two hydrogen atoms on C-2 of 1-chloropropane. 20 In addition, reactions with E 0 (interchange) > 290 kJ/mol might be observed for photochemical and thermal activation methods that prepare reactants with energy greater than 400 kJ/mol.…”
Section: R a F Tmentioning
confidence: 99%
“…It was also shown that a Br-CH 3 interchange mechanism was more likely than the Wagner-Meerwein mechanism for (CH 3 ) 3 CCH 2 Br. 20 Finally, the interchange of Cl with CH 3 was suggested to explain the decomposition of 1,1-dichloroacetone. 21 The experimental observation of the halogen-halogen and halogen-methyl interchange reactions leads to the question of whether or not pseudohalogens 22…”
Section: Introductionmentioning
confidence: 99%
“…Similar transition-state structures and energetics have been found for other systems by Holmes and co-workers as well as others; these include not only doubly bridged species with halogen, 4,6,7,[9][10][11][12][13]15 but ones with chlorine and methyl. 5,8 Turning to examples containing silicon, there also are cases of dihalogen exchange across a carbon−silicon single bond. 2,16 These typically are first-order reactions, but the nature of their "concertedness" often is not addressed.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Holmes and co-workers have studied a large variety of 1,2-rearrangement reactions occurring across a carbon–carbon single bond. Such studies emphasize understanding the dynamics and product distributions, particularly in systems interchanging halogen atoms through doubly bridged transition states. Unimolecular processes in these systems lead to rearranged as well as elimination products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation